Media and Mass Communication in a Frankfoot School Perspective. - GUASEMI, Brahim (Social Sciences Journal)
The Frankfurt School philosophers built their philosophy on a critical vision of the reality of contemporary, contradictory societies. At a time when science and technology knew extraordinary and rapid developments, human relations witnessed a serious setback that reached a state of chaos, primitiveness, and violence that posed a threat to human significance, value, and existence, in light of a society in which social diseases such as introversion, isolation, fanaticism, and alienation that led to exacerbation worsened. Perhaps the strange thing is that at a time when the means of communication have developed, which means better possibilities for human communication, we find that human relations have entered a stage of apathy, and society has become suffering from internal ruptures, due to the spread of individualism, monopoly, selfishness, and unfair competition that everyone mocks. The most extreme moral means., The contemporary lifestyle no longer accommodates the human condition, as much as it has come to evaluate a person according to the mechanisms of evaluating things and commodities, and therefore it will not be strange for cultural behavior to turn into a kind of harsh reflection of what the contemporary mind has come to. One of the tasks of this school was to criticize the modern mind in order to understand the real reasons that led the modern man to fall into the circle of irrationality, and the emergence of a new type of rationality colluding with technical ideology, which is what is called (instrumental rationality). That is “the mind that is used as a tool to achieve the benefit, a pragmatic mind whose only concern is summed up in the content or value of what it produces. In other words, contempt for the effective mind will necessarily lead to the decline of the concept of (authentic reason), if we do not say its destruction.” This means that the modern mind has deviated from its message to goals that serve power and ideologies of control and domination.